APAKAH TERDAPAT HUBUNGAN SIGNIFIKAN ANTARA PENYALURAN KUR DAN PERTUMBUHAN KREDIT UMKM PADA REGIONAL JAWA? - Ahmad Rifai; Muhammad Hafizh Ridha; Ninggar Resti Cahyani (JURNAL INFO ARTHA, 2024)
People's Business Credit (KUR) is the main policy instrument in supporting Micro, Small, and Medium Enterprises (MSMEs) in Indonesia where MSMEs have an important impact on economic growth and reducing regional disparities. This study aims to investigate the relationship between KUR distribution and MSME credit growth in the Java region in Indonesia. This study was conducted by collecting secondary data, historical data on KUR distribution, MSME credit growth data, and regional economic data for the period 2015 to 2022. Regression analysis and other statistical techniques were used to identify the relationship. The results of this study indicate that KUR distribution is not related to MSME credit growth in the Java region, while commercial credit is positively related to MSME credit growth in the Java region. The results of this study have significant policy implications where the government needs to emphasize a region-focused approach in designing KUR distribution policies to support sustainable MSME credit growth in Indonesia.